DYNAMICS OF SQUID FISHERIES BASED ON THE SUNGAILIAT NUSANTARA FISHING PORT, BANGKA BELITUNG PROVINCE: DINAMIKA PERIKANAN CUMI-CUMI YANG BERBASIS DI PELABUHAN PERIKANAN NUSANTARA SUNGAILIAT, PROVINSI BANGKA BELITUNG - Dianti, Sari Rama; Wahyuningrum, Prihatin Ika; Nurani, Tri Wiji; Mustaruddin, Mustaruddin; Apriliani, Izza Mahdiana (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The Nusantara Fishing Port (NFP) in Sungailiat is one of the landing sites for squid catches, with production tending to decline in the 2017–2021 period. The decline in squid production is thought to be influenced by exploitation pressure, climate change, and marine tin mining activities. The sustainability of squid is threatened, given their high sensitivity to changes in water conditions. The study aims to describe squid fishing gear at Sungailiat NFP and analyze the ecological dynamics of squid fisheries in the waters of Bangka Belitung during the period 2017–2021. Fishing unit data were obtained through observation and interviews with fishermen, while oceanographic data were obtained from remote sensing imagery. Data analysis included descriptive analysis, CPUE analysis, fishing season index analysis, and temporal analysis. The results showed that the main fishing gear used for squid in the Sungailiat NFP was handline, dominated by fishing boats ≤ 5 GT. The average CPUE value was higher in the east monsoon season than in the west monsoon season. The peak fishing season occurred from August to November. Chlorophyll-a distribution was higher during the eastern season, sea surface temperature was relatively warm during the eastern season until the transition, and salinity was within the optimal range (± 31.5–33.0 PSU). The interaction between oceanographic factors and the fishing season affects the dynamics of squid catches in the waters of Bangka Belitung.